2012
DOI: 10.1167/12.8.13
|View full text |Cite
|
Sign up to set email alerts
|

The role of presentation method and depth singletons in visual search for objects moving in depth

Abstract: Are objects moving in depth searched for efficiently? Previous studies have reported conflicting results, with some finding efficient search for only approaching motion (Franconeri & Simons, 2003), and others reporting that both approaching and receding motion are found more efficiently than static targets (Skarratt, Cole, & Gellatly, 2009). This may be due to presentation protocol differences and a confounding variable. We systematically tested the effect of the motion-in-depth presentation method and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Here, together with the fully significant effect of target-position, the right LOC also showed a marginal effect of "bmC > mC" (not significant after correction for multiple comparisons but observed both in the main and the control analyses; see Table IV) indicating a possible contribution of binocular signals also in the detection phase of the trial. The latter would be consistent with previous studies showing that targets including binocular disparity can facilitate visual search, over monocular cues only [Finlayson, et al, 2012].…”
Section: Discussionsupporting
confidence: 92%
“…Here, together with the fully significant effect of target-position, the right LOC also showed a marginal effect of "bmC > mC" (not significant after correction for multiple comparisons but observed both in the main and the control analyses; see Table IV) indicating a possible contribution of binocular signals also in the detection phase of the trial. The latter would be consistent with previous studies showing that targets including binocular disparity can facilitate visual search, over monocular cues only [Finlayson, et al, 2012].…”
Section: Discussionsupporting
confidence: 92%
“…Even though there are some results that do not confirm this observation (e.g., Theeuwes et al, 1998; Dent et al, 2012; Finlayson et al, 2012) there is a growing amount of reports revealing that targets presented closer to an observer result in faster RT (e.g., Shulman et al, 1979; Downing and Pinker, 1985; Gawryszewski et al, 1987; Chen et al, 2012; Finlayson and Grove, 2015; Plewan and Rinkenauer, 2016; Wang et al, 2016). However, comparisons of different studies on 3D perception are particularly difficult as those studies employ distinct techniques to induce depth impression.…”
Section: Discussionmentioning
confidence: 98%
“…However, we cannot rule out an alternative interpretation that the congruency bias seen in Experiment 1 was due to combined depth and disparity information, and that binocular depth but not monocular depth biases the perception of object features. Binocular disparity is arguably one of the stronger and more realistic cues for depth perception (Finlayson, Remington, & Grove, 2012; McKee & Taylor, 2010), and Finlayson et al (2012) demonstrated that there is variation in the perception of motion in depth depending on the cues used to simulate depth. That said, in both Experiments 1 and 2 we found RT priming effects for depth, as expected based on previous 3D attention literature (Atchley et al, 1997; Downing & Pinker, 1985), indicating that participants perceived and were sensitive to depth information in both cases.…”
Section: 0 General Discussionmentioning
confidence: 99%